International antitrust institutions - Oliver Budzinski (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2012)
The paper discussed the economic theory of international antitrust institutions. Economic theory shows that non-coordinated competition policies of regimes that are territorially smaller than the international markets on which business companies compete violate cross-border allocative efficiency and are deficient with respect to global welfare. At the same time, some diversity of antitrust institutions and policies promotes dynamic and evolutionary efficiency so that globally binding, worldwide homogenous competition rules do not represent a first-best solution either. After reviewing the existing international antitrust institutions and their prospects and limits from an economic perspective (with a focus on the International Competition Network, ICN), the paper discusses reform proposals from economic literature.
Keywords: F02; F53; F55; K21; L40; D02; 330; international competition policy; international antitrust; International; Competition Network; global governance; WTO; institutions; international organizations